Teachers-Students’ Interaction in Early Childhood Inclusion Program - Novitayanti, Lili; Tirtayani, Luh Ayu (LPPM Undiksha, 2019)
UNESCO has defined inclusive education as a chance for children with disabilities to learn in the same class with their non-disable peers. It becomes the most equitable chance for those school age students with disabilities to get their right. The implementation of early childhood inclusion programs in Bali is relatively new. Thus, an analysis on its implementation is needed in order to know in extend the program is effective. This study aims to describe the effectiveness of the teachers-students social interaction in early childhood inclusion program. It is an evaluative research by focusing on the learning process, including aspects of plan, implementation, and assessment. There are 119 respondents, who are headmasters and teachers of Kindergarten, involved in this study. Data are collected through questionnaire that have been tested for being validated. The result shows that social interaction of teachers and students are: (1) positive from the aspect of planning with F + = 53.781% and F? = 46.218%, (2) not effective in the aspect of implementation with F + = 47.058% and F? = 52.941%, and (3) not effective social in the aspect of evaluation with F + = 42.857% and F? = 57.142%. It can be concluded that the social interaction of teachers and students in inclusion early childhood education program in is less effective (+ ? ?). The teacher-students? social interaction as pivotal aspect of learning process, especially for special need students, needs to improve.